Not your father's MBA [technology management degree programs]. - Karlin, S. (IEEE spectrum)
The last two decades have seen a change in traditional MBA programs to give way to graduate degrees tailored to the business world's increasing emphasis on technology, global expansion and the rise in entrepreneurship. At the same time, new MBA programs are striving to accommodate the working engineers' need for flexible class schedules and relevant curricula, as more midcareer professionals enter managerial positions. There are currently more than 100 engineering management programs which teach engineers how to bring together different disciplines and practice engineering in a team environment. As the business world becomes increasingly multinational, management training programs are also taking a more global outlook. US business schools have formed alliances, satellite campuses and joint and exchange programs with non-US universities to give students the experience of tackling complex business and technical concepts in an international setting. Many MBA programs also give students the option of distance learning through mailed class work and learning guides as well as access to study groups and tutors via the Internet, video conferencing, phone and fax. Cooperation between academia and industry is expected to become more prevalent as companies continue to streamline manufacturing.